Pengenalan Bentuk dan Pola Suara bagi Anak Anak Penyandang Tuna Rungu - Ariyono Setiawan (Jurnal Penelitian)
IInability to speak for the Deaf child is a distinctive characteristic that makes it different from normal children. Children with normal hearing understand the language through hearing in the months before they start talking. Speech recognition or recognition of voice patterns in children Deaf as search forms grades suitability and appropriateness. the type of sound is a development from techniques and systems that enable the computer to accept input in the form of patterns spoken word so on get the value of the type of words approaches, and can be understood. This study proposes a solution in Method utilizes biometrics to recognize the type of sound patterns deaf children who will be in the skewer with the sound of a normal child. Biometric methods used in digital signal processing (in this case sound) in the form of discrete biometrics refers to the automatic identification of humans by psikological or basic human characteristic sound.